EVALUASI KEIKUTSERTAAN LABORATORIUM UJI DAN KALIBRASI PRTBBN PADA UJI PROFISIENSI / UJI BANDING SESUAI PERSYARATAN ISO/IEC 17025:2017 - Zaidi Oktari; Masripah; Septi Septi Rizkine Pramukti; Mustika Fadila (Jurnal Penjaminan Mutu, 2023)
ISO /IEC 17025:2017 requires all accredited laboratories to take part in proficiency and interlaboratory testing activities. This research discussed the evaluation of the Nuclear Fuel Installation (IBBN) Laboratory’s participation in proficiency and interlaboratory testing within the last 3 years. The research was carried out by monitoring the achieved target and quality goals, monitoring the numbers of scope/equipment that had taken a part in proficiency and interlaboratory testing, then examining the existing problem by finding the root cause using the fishbone method, and providing some recommendations for improvement and preventive action. Based on 2019-2021 data, quantitatively speaking, the participation of IBBN in proficiency and interlaboratory testing has met the quality goals, which is 2 scopes/equipment per year. However, in general, the percentage of IBBN participation is still low, only 43% or only 6 scopes from 14 total scopes which already taken part. Recommended improvements include the identification of other laboratories outside Ind with the same scope, management’s commitment for funding support, and funding support, as well as increasing personnel competencies related to proficiency and interlaboratory testing.